2022
DOI: 10.1002/anie.202200823
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐Controlled Condensation of [Mo2O5(PTC4A)2]6− Metalloligand in Stepwise Assembly of Hexagonal and Rectangular Ag18 Nanoclusters

Abstract: Stepwise assembly starting from a preassembled metalloligand is a promising approach to obtain otherwise unattainable silver nanoclusters, but hard to be intrinsically identified due to the lack of convincing evidence to justify such a process. Herein, hexagonal and rectangular Ag 18 nanoclusters are constructed from the [Mo 2 O 5 (PTC4A) 2 ] 6À (H 4 PTC4A = p-phenylthiacalix[4]arene) metalloligand through stepwise assembly. The formation of the metalloligand is confirmed by electrospray ionization mass spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…The results showed that the temperature of both compounds remarkably increased within 3 s at various power densities from 0.1 to 0.5 W cm –2 (Figure a). For example, at 0.5 W cm –2 , the temperature soared from 23 to 470 and 512 °C for Ag48M and Ag48T , respectively, and the corresponding heating rate (149 °C s –1 for Ag48M and 163 °C s –1 for Ag48T ) is much higher than most reported photothermal materials (Table S10), demonstrating the excellent photothermal conversion properties of both polymorphs . Before the measurement, the photothermal performance of Ag48M was expected to be better than that of Ag48T due to the weaker radiative decay (Figure S14).…”
Section: Resultsmentioning
confidence: 94%
“…The results showed that the temperature of both compounds remarkably increased within 3 s at various power densities from 0.1 to 0.5 W cm –2 (Figure a). For example, at 0.5 W cm –2 , the temperature soared from 23 to 470 and 512 °C for Ag48M and Ag48T , respectively, and the corresponding heating rate (149 °C s –1 for Ag48M and 163 °C s –1 for Ag48T ) is much higher than most reported photothermal materials (Table S10), demonstrating the excellent photothermal conversion properties of both polymorphs . Before the measurement, the photothermal performance of Ag48M was expected to be better than that of Ag48T due to the weaker radiative decay (Figure S14).…”
Section: Resultsmentioning
confidence: 94%
“…This is consistent with the distances in related silver clusters and almost identical to those in silver metal. [65] The whole structure of compound 1 shows an ellipsoidal shape. The central CO 3 2À ion plays a crucial role in building the structure of compound 1.…”
Section: Crystal Structure Description Of Compoundmentioning
confidence: 99%
“…Thiacalix[4]­arene (TC4A), which has many preorganized synergetic coordination sites compared to these ligands with a single coordination site, has a stiff shell that shields a metallic core and may have an added stabilizing impact on Ag NCs. However, most TC4A-protected Ag clusters were synthesized using oxoanions as templates, such as Ag 18 , Ag 36 , Ag 42 , Ag 47 , Ag 49 , and Ag 88 . As far as we are aware, only four TC4A-protected Ag 1/0 superatoms, viz., Ag 21 , Ag 34 , and Ag 35 with eight valence electrons, ,, and Ag 155 with 92 valence electrons, have been structurally characterized until now . They are all in the closed-shell “magic” number series for valence electron numbers.…”
Section: Introductionmentioning
confidence: 99%